Pre-rehabilitation of patients before surgery - proposed procedure - Filarecka, Agnieszka; Leksowski, Łukasz; Biernacki, Maciej (Journal of Education, Health and Sport, 2022)
Objectives. Surgical procedures are one of the invasive treatment methods in modern medicine. Procedural medicine develops from year to year. The method of invasive treatment depends primarily on the disease entity. Mostly, it will be minimally invasive surgery. Regardless of the invasive nature of the procedure, the patient requires temporary immobilization, which is associated with postoperative complications. Material and methods. A review of the available literature and own observations were used for the study. Results. The available literature primarily focuses on the number of postoperative complications and the relationship between their occurrence and preoperative prophylaxis. There are numerous references in the literature concerning the emergence of respiratory and circulatory failure after surgery, especially in obese patients and patients with comorbidities. Conclusions. The implementation of pre-rehabilitation is necessary as a prevention of postoperative complications.